Effect of Endogenous Clostridioides difficile Toxin Antibodies on Recurrence of C. difficile Infection. (19th October 2019) - Kelly, Ciarán P; Poxton, Ian R; Shen, Judong; Wilcox, Mark H; Gerding, Dale N; Zhao, Xuemei; Laterza, Omar F; Railkar, Radha; Guris, Dalya; Dorr, Mary Beth
Abstract: Background: Endogenous antibodies (eAbs) against Clostridioides ( Clostridium ) difficile toxins may protect against recurrence of C. difficile infection (rCDI). This hypothesis was tested using placebo group data from MODIFY (Monoclonal Antibodies for C. difficile Therapy) I and II (NCT01241552 and NCT01513239, respectively), global, randomized phase 3 trials that assessed the efficacy and safety of the antitoxin monoclonal antibodies bezlotoxumab and actoxumab in participants receiving antibiotic therapy for CDI. Methods: A placebo infusion (normal saline) was administered on study day 1. Serum samples were collected on day 1, week 4, and week 12, and eAb-A and eAb-B titers were measured by 2 validated electrochemiluminescence immunoassays. Rates of initial clinical cure and rCDI were summarized by eAb titer category (low, medium, high) at each time point. Results: Serum eAb titers were available from a total of 773 participants. The proportion of participants with high eAb-A and eAb-B titers increased over time. Rates of initial clinical cure were similar across eAb titer categories. There was no correlation between eAb-A titers and rCDI rate at any time point. However, there was a negative correlation between rCDI and eAb-B titer on day 1 and week 4. rCDI occurred in 22% of participants with high eAb-B titers at baseline compared with 35% with low or medium titers ( P = .015). Conclusions: Higher eAb titers against toxin B, but not toxin A, were associated with protection against rCDI. These data are consistent with the observed efficacy of bezlotoxumab, and lack of efficacy of actoxumab, in the MODIFY trials. Clinical Trials Registration: NCT01241552 and NCT01513239. Abstract : High titers of endogenous antibodies to Clostridioides difficile toxin B, but not toxin A, were associated with reduced recurrence of C. difficile infection. These findings are consistent with efficacy data from the phase 3 MODIFY trials of bezlotoxumab and actoxumab.